FADAC Hamburg 1.0: Guide to the Faroese Danish Corpus Hamburg - Debess, Iben Nyholm (Christian-Albrechts-Universität zu Kiel, 2019)
This paper provides a short description of the Faroese Danish Corpus Hamburg (FADAC Hamburg), Version 1.0, which can be accessed online via the permanent identifier (PID) http://hdl.handle.net/11022/0000-0007-D0D5-D. FADAC Hamburg is a corpus corpus of spoken, informal Faroese and Faroese Danish (469,000 words) that has been collected as part of the project Variation in the Multilingualism on the Faroe Islands (Project K8) at the Research Centre on Multilingualism at the University of Hamburg. Earlier versions (numbered 0.2) of FADAC Hamburg subcorpora (FADAC-DAN and FADAC-FAR) were published online through the Hamburg Center for Language Corpora in cooperation with the Specialist Information Service Northern Europe at Kiel University Library. Due to technical problems, however, access was limited to smaller parts of the data. The current version was prepared as part of a project at Kiel University, which aimed at converting legacy corpus data into sustainable formats and ensuring internal consistency. The corpus is intended for use with EXMARaLDA (exmaralda.org).